A New Tillandsia (Tillandsioideae, Bromeliaceae) Species from the Copalita River Canyon, Oaxaca, Mexico - Flores-Cruz, María; Vázquez-Hurtado, Nora Berenice; Torres-Colín, Rafael; Tinoco-Berrios, Ingrid Magali; Granados Mendoza, Carolina (Phytotaxa, 2020)
A new saxicolous species from the steep cliffs of the Copalita river canyon is described and illustrated: Tillandsia joel-mandimboensis. We present detailed morphological comparisons of the new species to other morphologically-related saxicolous Tillandsia species also endemic to river canyon cliffs, complemented with information on their habitat preferences, geographical distribution and phenology.